An approach to estimate the life-cycle cost of energy efficiency improvement of room air conditioners - Mahlia, Teuku Meurah Indra; Saidur, Rahman; Husnawan, M.; Masjuki, Haji Hassan; Kalam, M.A. (Sila Science, 2010)
This paper presents an approach to calculate life-cycle cost analysis of energy efficiency improvement of room air conditioners. The least efficient model from a survey in the market is selected for sample calculation. The method includes the selection of a set of design options that increase efficiency, life cycle cost (LCC) analysis and payback period. LCC is analyzed as a function of seven design options and five variables, namely discount rate, fuel price, appliance lifetime, incremental cost and potential efficiency improvement. The study found that, certain level of efficiency improvement can be achieved, if manufacturers willing to adopt more efficient design options with a little additional investment for the product. Furthermore, the method can be used for other appliances without any major modification.